Return of the lysergamides. Part II: Analytical and behavioural characterization of N6‐allyl‐6‐norlysergic acid diethylamide (AL‐LAD) and (2'S, 4'S)‐lysergic acid 2, 4‐dimethylazetidide (LSZ). Issue 1 (6th June 2016) - Brandt, Simon D.; Kavanagh, Pierce V.; Westphal, Folker; Elliott, Simon P.; Wallach, Jason; Colestock, Tristan; Burrow, Timothy E.; Chapman, Stephen J.; Stratford, Alexander; Nichols, David E.; Halberstadt, Adam L.
Abstract : Lysergic acid N, N ‐diethylamide (LSD) is perhaps one of the most intriguing psychoactive substances known and numerous analogs have been explored to varying extents in previous decades. In 2013, N 6 ‐allyl‐6‐norlysergic acid diethylamide (AL‐LAD) and (2' S, 4' S )‐lysergic acid 2, 4‐dimethylazetidide (LSZ) appeared on the 'research chemicals'/new psychoactive substances (NPS) market in both powdered and blotter form. This study reports the analytical characterization of powdered AL‐LAD and LSZ tartrate samples and their semi‐quantitative determination on blotter paper. Included in this study was the use of nuclear magnetic resonance (NMR) spectroscopy, gas chromatography‐mass spectrometry (GC‐MS), low and high mass accuracy electrospray MS(/MS), high performance liquid chromatography diode array detection and GC solid‐state infrared analysis. One feature shared by serotonergic psychedelics, such as LSD, is the ability to mediate behavioural responses via activation of 5‐HT2A receptors. Both AL‐LAD and LSZ displayed LSD‐like responses in male C57BL/6 J mice when employing the head‐twitch response (HTR) assay. AL‐LAD and LSZ produced nearly identical inverted‐U‐shaped dose‐dependent effects, with the maximal responses occurring at 200 µg/kg. Analysis of the dose responses by nonlinear regression confirmed that LSZ (ED50  = 114.2 nmol/kg) was equipotent to LSD (ED50  = 132.8 nmol/kg) in mice, whereas AL‐LAD was slightly less potent (ED50  = 174.9 nmol/kg). The extent to which a comparison in potency can be translated directly to humans requires further investigation. Chemical and pharmacological data obtained from NPS may assist research communities that are interested in various aspects related to substance use and forensic identification. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : AL‐LAD and LSZ emerged in 2013 on the 'research chemicals' market. This study presents a comprehensive analytical characterization of powdered material and blotters. Consistent with other serotonergic hallucinogens, both compounds displayed LSD‐like properties in mice when employing the head‐twitch response (HTR) assay. Analysis of the dose‐responses confirmed that LSZ (ED50  = 114.2 nmol/kg) was equipotent with LSD (ED50  = 132.8 nmol/kg), whereas AL‐LAD was slightly less potent (ED50  = 174.9 nmol/kg).